Penerapan Model Pembelajaran Talking Stick Untuk Meningkatkan Keaktifan Belajar Matematika Siswa Pada Materi Himpunan di Kelas VII - Mhd. Syukri Harisandi; Nova Christina Dewi; Susi Sulastri Lubis (Program Studi Matematika Universitas Graha Nusantara Padangsidimpuan, 2025)
This study aims to determine whether there is a significant effect of using the Talking Stick learning model on students' mathematics learning outcomes on set material at SMP Negeri 4 Padangsidimpuan, Padangsidimpuan City on set subject matter. This study used a Non-Equivalent Group Design with one type of treatment where in this study only the experimental class was given treatment while the control class was not given treatment. The samples in this study were two classes taken from the population using the Total Sampling technique. Total Sampling (Saturated Sampling). The samples in this study were students in grades VII-8 and VII-9 of SMP Negeri 4 Padangsidimpuan Padangsidimpuan City in the 2023-2024 school year. the data collection instrument used was a test. The results of research using the Talking Stick learning model on set material in class VII SMP Negeri 4 Padangsidimpuan Padangsidimpuan City. It is known that t-count> t-table (2.194> 2.002) means Ha is accepted and H0 is rejected. So it can be concluded that: There is a Significant Effect on the Use of the Talking Stick Learning Model on Student Mathematics Learning Outcomes in Class VII of SMP Negeri 4 Padangsidimpuan, Padangsidimpuan City.